Motherhood as an athletic career transition in female Olympic athletes - Roberts, C.-M.; Kenttä, G. (Women in Sport and Physical Activity Journal, 2018)
Background: Motherhood has been deemed incompatible with an athletic career, with women encouraged to end their involvement in sport to have children. However, there are a growing number of women who achieve both personal and high-performance sport goals. For these women, having a child during the course of a sport career can be viewed as an athletic career transition - one that causes a significant interruption to their career trajectory, bringing with it a unique set of demands that requires coping processes to allow a return to elite sport.